The bookshop rescue - Alers, Rochelle (Furever yours., 2022)
Bookshop owner--and recently heartbroken--Lucy Tucker never imagined how dramatically life would change once she started fostering Buttercup, a pregnant golden retriever. The biggest change? Growing a lot closer to the businessman next door, Calum Ramsey, especially after the two of them help Buttercup welcome her five puppies into the world. One romantic night later, and they're expecting a baby of their own! Stunned at first, steadfastly single Calum is now dutifully offering marriage. But Lucy doesn't need rescuing. She wants the true-blue happy ending they both deserve.